2014
DOI: 10.1111/jog.12505
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss: An unknown complication of pre‐eclampsia?

Abstract: Pre-eclampsia is a potential risk factor for cochlear damage and sensorineural hearing loss. Further studies that include routine audiological examinations are needed in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Se ha descrito el efecto de enfermedades propias del embarazo sobre la audición. Terzi et al (15) realizaron un estudio caso-control prospectivo en el que compararon a pacientes embarazadas con diagnóstico de preeclampsia versus pacientes embarazadas normotensivas. Durante el tercer trimestre de embarazo todas fueron evaluadas con audiometría tonal pura y emisiones otoacústicas transcientes y concluyeron que la preeclampsia es un factor de riesgo para daño coclear e hipoacusia sensorio-neural.…”
Section: Cambios Auditivos Patológicos Durante El Embarazounclassified
“…Se ha descrito el efecto de enfermedades propias del embarazo sobre la audición. Terzi et al (15) realizaron un estudio caso-control prospectivo en el que compararon a pacientes embarazadas con diagnóstico de preeclampsia versus pacientes embarazadas normotensivas. Durante el tercer trimestre de embarazo todas fueron evaluadas con audiometría tonal pura y emisiones otoacústicas transcientes y concluyeron que la preeclampsia es un factor de riesgo para daño coclear e hipoacusia sensorio-neural.…”
Section: Cambios Auditivos Patológicos Durante El Embarazounclassified
“…The findings indicate that PE has an adverse effect on the cochlear function by inducing the dysfunction of outer hair cells [ 8 ]. In addition, it was reported that patients with PE have a significantly higher hearing threshold than normal subjects [ 9 ]. Considering these studies’ findings, it can be suggested that PE has significant pathological outcomes in otology and nephrology, ophthalmology, cardiology, and neurology.…”
Section: Introductionmentioning
confidence: 99%